Effects of natural clay on ionic conductivity, crystallinity and thermal properties of PEO-LiCF3SO3-natural clay as solid polymer electrolyte nanocomposites - Pattranuch Pongsuk (2019)
© 2019 Trans Tech Publications Ltd, Switzerland. The polymer nanocomposites of PEO-LiCF3SO3 based solid polymer electrolyte were prepared using two kinds of natural clays, which are halloysite nanotube (HNT) and montmorillonite (MMT) nanoparticle. Different contents (0, 1, 5 and 10wt %) of halloysite nanotube (HNT) and montmorillonite (MMT) nanoparticle were explored. Solid polymer electrolyte nanocomposite film was prepared by solution casting method. The ionic conductivity, crystallinity and thermal properties of solid polymer electrolyte membranes were studied by impedance spectroscopy, X-ray diffraction (XRD) and differential scanning calorimetry (DSC), respectively. It was found that HNT provided higher ionic conductivity for solid polymer electrolyte nanocomposite than what MMT did. The highest ionic conductivity at room temperature was found at 5% HNT as 2.068 x 10-5 S.cm-1. The ion-polymer interactions between PEO-LiCF3SO3 and natural clay nanoparticle were investigated by using Fourier transform infrared (FTIR) spectra. The PEO-LiCF3SO3-5%HNT showed good oxidative stability than PEO-LiCF3SO3 composite.